2021
DOI: 10.1007/s00521-021-06312-z
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of rural financial ecological environment based on machine learning and improved neural network

Abstract: In order to improve the effect of rural financial ecological environment evaluation, this paper combines machine learning and improved neural network algorithms to construct a rural financial ecological environment evaluation system. First, this paper optimizes the input layer structure and its initial weight random assignment. The input layer structure is processed by factor analysis, and the initial weight random assignment is optimized by particle swarm optimization. Secondly, this paper constructs a rural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…A good financial ecological environment can promote the healthy and efficient development of the financial system [9], thus attracting capital accumulation and reducing operating costs [10]. King and Levine, who built an evaluation index system and a rural credit risk early-warning model based on their research on rural financial development, rural economic development, and the rural credit legal environment, found that rural credit information asymmetry is the main factor leading to rural credit risk [11].…”
Section: Literature Reviewmentioning
confidence: 99%
“…A good financial ecological environment can promote the healthy and efficient development of the financial system [9], thus attracting capital accumulation and reducing operating costs [10]. King and Levine, who built an evaluation index system and a rural credit risk early-warning model based on their research on rural financial development, rural economic development, and the rural credit legal environment, found that rural credit information asymmetry is the main factor leading to rural credit risk [11].…”
Section: Literature Reviewmentioning
confidence: 99%
“…stock exchange [7], law enforcement department [8], ecology [9], human resource management [10], signal processing with blind separation [11], and cybersecurity [12]. The ANNs are mainly based on mathematical models inspired by biological nervous systems, such as the brain's route information.…”
Section: Introductionmentioning
confidence: 99%
“…Several applications of machine learning algorithms have been made for financial business [8][9][10], and for the automatic risk assessment in the financial environment [11,12], with good results. However, despite the efforts made by researchers, there is no one best machine learning algorithm for all classification problems, as stated in the "no free lunch" theorems [13].…”
Section: Introductionmentioning
confidence: 99%